Topochemistry‐Driven Synthesis of Transition‐Metal Selenides with Weakened Van Der Waals Force to Enable 3D‐Printed Na‐Ion Hybrid Capacitors. (9th December 2021) - Zong, Wei; Guo, Hele; Ouyang, Yue; Mo, Lulu; Zhou, Chunyang; Chao, Guojie; Hofkens, Johan; Xu, Yang; Wang, Wei; Miao, Yue‐E; He, Guanjie; Parkin, Ivan P.; et al.
Abstract: Hybrid capacitors exhibit promise to bridge the gap between rechargeable high‐energy density batteries and high‐power density supercapacitors. This separation is due to sluggish ion/electron diffusion and inferior structural stability of battery‐type materials. Here, a topochemistry‐driven method for constructing expanded 2D rhenium selenide intercalated by nitrogen‐doped carbon hybrid (E‐ReSe2 @INC) with a strong‐coupled interface and weak van der Waals forces, is proposed. X‐ray absorption spectroscopy analysis dynamically tracks the transformation from ReO into ReC bonds. The bridging bonds act as electron transport channels to enable improved conductivity and accelerated reaction kinetics. The expanded interlayer‐spacing of ReSe2 layer by INC facilitates ion diffusion and ensures structural stability. As expected, the E‐ReSe2 @INC achieves an improved rate capability (252.5 mAh g −1 at 20 A g −1 ) and long‐term cyclability (89.6% over 3500 cycles). Moreover, theoretical simulations reveal the favorable Na + storage kinetics can be ascribed to its low bonding energy of −0.06 eV and diffusion barrier of 0.08 eV for sodium ions. Additionally, it is demonstrated that 3D printed sodium‐ion hybrid capacitors deliver high energies/power densities of 81.4 Wh kg −1 /0.32 mWh cm −2 and 9992.1 W kg −1 /38.76 mW cm −2, as well as applicability in a wide temperature range. Abstract : The expanded rhenium selenide intercalated by nitrogen‐doped carbon hybrid with a strong‐coupled interface and weak van der Waals forces is prepared by topochemistry driven synthesis. The structural evolution is dynamically tracked from ReO into ReC bonds. The bridging bonds can act as electron transport "bridge" and supporting "pillar" between ReSe2 interlayer and INC, enabling improved electrical conductivity and ion diffusion coefficient.